PENGARUH BEBERAPA VARIETAS DAN JUMLAH BIBIT TERHADAP PERTUMBUHAN DAN PRODUKSI PADI SAWAH (Oryza sativa L.) DENGAN METODE HAZTON - dea, Dea Musvita; Iswahyudi; Boy Riza Juanda (Jurnal Penelitian Agrosamudra, 2023)
The purpose of this study was to determine the influence of several varieties and the number of seeds on the growth and production of paddy rice with the Hazton method, and to determine the interaction between the number of seeds and varieties of paddy rice on the Hazton method. This research was conducted in the rice fields of Alue Merbau Village, East Langsa District, Langsa City, when the research was carried out in early July to October 2021. This study used a factorial Randomized Group Design (RAK) consisting of 2 factors, namely: factor in the type of rice variety (V) which consists of 3 types, namely: V1= Ciherang, V2= Inpari 32, V3 = Inpari 45. The factor of the number of seedlings (J) consists of 3 levels, namely: J1 = 20 seedlings, J2 = 30 seedlings, J3 = 40 seedlings. The parameters observed include: plant height, number of saplings, age of panicle exit, number of productive saplings, panicle length, harvest age, amount of grain, percentage of grain filled and empty, weight of 1,000 grains of grain, and grain production per clump.